2014
DOI: 10.1017/s0007114514000841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary α-lipoic acid on the mRNA expression of genes involved in drug metabolism and antioxidation system in rat liver

Abstract: In the present study, the mRNA levels of hepatic proteins involved in the drug metabolism of rats fed α-lipoic acid were evaluated by DNA microarray and real-time PCR analyses. Experimental diets containing 0, 0·1, 0·25 and 0·5 % (w/w) α-lipoic acid were fed to four groups of rats consisting of seven animals each for 21 d. DNA microarray analysis revealed that the diet containing 0·5 % α-lipoic acid significantly (P< 0·05) increased the mRNA levels of various phase I drug-metabolising enzymes up to 15-fold and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Moreover, in a research carried out in rats, ALA/DHLA were shown to increase the mRNA expression of proteins involved in the redox system. Consistent with this protective activity, a dose dependent decrease of malondialdehyde concentrations was detected [68].…”
Section: An Overview On Some Specific Effects Of Alasupporting
confidence: 64%
“…Moreover, in a research carried out in rats, ALA/DHLA were shown to increase the mRNA expression of proteins involved in the redox system. Consistent with this protective activity, a dose dependent decrease of malondialdehyde concentrations was detected [68].…”
Section: An Overview On Some Specific Effects Of Alasupporting
confidence: 64%
“…Besides, the mRNA expression of HdhMT was also significantly increased with elevated expression of HdhMTF‐1, which was found to be Cd inducible in H. discus hannai (Lee & Nam, ). Similarly, dietary LA significantly increased the mRNA expression of metallothioneins ( Mt1a and Mt2A ) in rat liver (Ide, ). It has also been found that mouse metallothioneins ( Mt1 and Mt2 ) are overwhelming in response to transcriptional regulation of MTF‐1 when exposed to Cd (Wimmer, Wang, Georgiev, & Schaffner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers reported that dietary PUFA downregulated the expression of lipogenic enzymes [7,8] and enzyme synthesis with a decrease in hepatic fatty acid synthesis [9,10] in the rat liver.…”
Section: Introductionmentioning
confidence: 99%